Hypoxic mesenchymal stem cell secretome upregulates IL-10 and STAT3 gene expressions in mice model with polycystic ovary syndrome - Lusiana, Lusiana; Darlan, Dewi M.; Trisnadi, Setyo; Putra, Agung; Amalina, Nur D.; Husain, Sofian A. (Narra X, 2024)
Polycystic ovary syndrome (PCOS) is a condition characterized by chronic anovulation and hyperandrogenism, which often leads to infertility. It is closely associated with chronic inflammation triggered by glucose and saturated fat, contributing to hyperandrogenism and negatively impacting a patient’s quality of life. Effective therapeutic approaches are essential to address these issues. The secretome of mesenchymal stem cells (MSCs) have demonstrated the ability to suppress pro-inflammatory cytokine secretion and regulate growth factors. The aim of this study was to investigate the effect of hypoxic mesenchymal stem cell secretome (MHSSCs) on the expression of interleukin-10 (IL-10) and signal transducer and activator of transcription 3 (STAT3) genes in a PCOS-induced mouse model. An in vivo experimental study was conducted using a post-test-only control group design. A total of 24 female C57BL/6 mice were divided into four groups: healthy control, negative control (PCOS mice injected with 0.9% NaCl), T1 (PCOS mice administered 200 μL of MHSSCs), and T2 (PCOS mice administered 400 μL of MHSSCs) for 33 days. Gene expression of IL-10 and STAT3 were quantified using quantitative reverse transcription polymerase chain reaction (qRT-PCR), normalized to the expression of the housekeeping β-actin gene. Statistical analysis using one-way ANOVA followed by the least significant difference (LSD) post-hoc test was then performed. The results showed a significant increase in IL-10 expression in the T2 group compared to the negative control group (p<0.001). STAT3 expression was also significantly higher in the T2 group compared to the negative control group (p=0.035). A dose-dependent effect was observed, with the T2 group demonstrating the highest upregulation of both IL-10 and STAT3 expression levels. The study highlights that the administration of MHSSCs effectively increased IL-10 and STAT3 gene expression, suggesting their potential as a therapeutic strategy to alleviate inflammation in PCOS.